Tinjauan Umum Mengenai Implementasi Keterbukaan Informasi Publik di Dinas Komunikasi dan Informatika Provinsi Sumatera Selatan - Rosalinda, Rosalinda (Lex Librum : Jurnal Ilmu Hukum, 2025)
This study examines the implementation of the Public Information Disclosure Policy (KIP) by the Communication and Informatics Office (Diskominfo) of Palembang City. Using a qualitative approach with purposive sampling, data were collected through interviews, documentation, and online sources, and analyzed through the stages of data collection, reduction, presentation, and conclusion drawing. The results indicate that the implementation of KIP has not been fully effective. Communication, bureaucratic structure, and implementer disposition show relatively good performance, whereas limited human resources and inadequate supporting facilities remain major obstacles. Despite these challenges, efforts to provide public information through social media and the official government website are routinely carried out. The study highlights the need to strengthen human resource capacity and improve supporting infrastructure to enhance the effectiveness of public information disclosure